University Students and their faculty: Perceptions of entrepreneurial optimism, overconfidence and entrepreneurial Intentions - Giacomin, Olivier; Janssen, Frank; Shinnar, Rachel (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2015)
While an entrepreneurial career requires some level of optimism and confidence, unfounded optimism and overconfidence can be detrimental to entrepreneurial success. By comparing student and faculty perceptual differences, we assess whether university students are overly optimistic regarding the outcomes they expect from an entrepreneurial career as well as overconfident in their perceptions of barriers to entrepreneurship. Findings suggest that, overall, students are more optimistic but not more confident than faculty. Also, students who are more optimistic and more confident than their faculty, also perceive themselves to be more entrepreneurial and have stronger entrepreneurial intentions than their peers.